Reasons for changes of passenger perceptions of low cost carriers identified on social media – a case study on Jetstar Airways – A literature review - Reddy, Ronal (Technium Social Sciences Journal, 2021)
Low-cost carriers have been operating since early 1990’s and the reputation of these low-cost carriers has been a questionable one. This literature review looks to understand the marriage between low-cost carrier Jetstar and social media/IT and how this is connected to understand customer perceptions of low-cost carrier Jetstar that operates within New Zealand. Jetstar operates around the world, but for the purpose of this literature review, we will be looking at perceptions based on Jetstar flying around New Zealand. This research uncovers what customers comment about low-cost carriers like Jetstar and how airline companies are alert about the comments made on their social media platforms. These comments are often based on many different factors which the literature review looks at e.g. perceptions based on inflight experience, perceptions based on events, perceptions based on the purpose of travel, and choices in the way of business for organisations. It is hoped that this literature review would benefit the airline to understand the stance of customers who choose to fly with Jetstar and the reason for their choices.